Gaya Kepemimimpinan Patrenalistik, Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Variabel Intervening Kepuasan Kerja Pada Perusahaan Keluarga - Faviandhani, Qausya; Karya, Denis Fidita; Widjaja, Resti Pringgadini Ari (LP3M STAI Darussalam Krempyang Nganjuk, 2018)
Family companies are an interesting phenomenon in the business world today, many companies in the world are family companies. Business development can not be separated from the leadership role that is applied from every leader in each generation, leadership succession greatly influences the continuity of family companies. In addition to leadership roles, employee performance is one determinant of the success of the company's goals. Other factors that influence employee performance are include patrenalistic leadership style, organizational culture, work environment and job satisfaction. This research aimed to analyze the effect of paternalistic leadership style, organizational culture and work environtment on employee’s performance with employee’s satisfaction as the intervening. This research was conducted in one of the private hospitals in East Java Pacitan Regency. The data collected from 25 respondents by using census. The data were analysed by using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The Result of this research showed that the effect of paternalistic leadership style and organizational culture, work environtement on employee’s satisfaction (as variable intervening) is positive and significant and the impact of employee’s satisfaction on employee’s performance is positive and significant.